2021
DOI: 10.1108/ihr-02-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Place attachment and brand loyalty: the moderating role of customer experience in the restaurant setting

Abstract: PurposeThe purpose of this study is to ascertain the effects of place attachment on brand loyalty. This study further ascertains whether the effects of emotion-based attachment on brand loyalty are stronger for customers who have a positive experience with a restaurant brand. Additionally, the authors investigate whether emotion-based attachment mediates the relationships between identity-based attachments, place dependence and brand loyalty in the restaurant setting.Design/methodology/approachThe authors admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 92 publications
3
35
0
1
Order By: Relevance
“…The statement is supported by Fitriani and Achmad (2021) who found that brand love mediates the effect of brand identification towards brand loyalty partially and positively. Meanwhile, full mediating role of brand love in predicting brand identification and brand loyalty is also known from the results of previous studies (Nyamekye et al, 2021;Kim & Lee, 2020). When customers feel the similarity of their self-concept with the brand, supported by the formation of emotional closeness (brand love), those feelings will motivate customers to make repeat orders consistently to one brand or signify the formation of high loyalty.…”
Section: Brand Love Mediating the Relationship Between Brand Identifi...mentioning
confidence: 92%
See 4 more Smart Citations
“…The statement is supported by Fitriani and Achmad (2021) who found that brand love mediates the effect of brand identification towards brand loyalty partially and positively. Meanwhile, full mediating role of brand love in predicting brand identification and brand loyalty is also known from the results of previous studies (Nyamekye et al, 2021;Kim & Lee, 2020). When customers feel the similarity of their self-concept with the brand, supported by the formation of emotional closeness (brand love), those feelings will motivate customers to make repeat orders consistently to one brand or signify the formation of high loyalty.…”
Section: Brand Love Mediating the Relationship Between Brand Identifi...mentioning
confidence: 92%
“…Customers will be more loyal to use brand that is able to raise their self-image through similar characteristics and self concepts (Shin, Back, Lee, & Lee, 2020). This DOI: http://dx.doi.org/10.24912/jm.v26i2.900 statement is supported by Nyamekye et al (2021) and Kim and Lee (2021) that brand identification can affect brand loyalty. However, there has been differences in research results, whereas brand identification doesn't affect brand loyalty (Fitriani & Achmad, 2021;Alnawas & Altarifi, 2015).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations